RASIONALITAS KONSUMSI DI MASA PANDEMI PERSPEKTIF ISLAM - Choiril Anam; Purnama Sariati (Istithmar: Jurnal Studi Ekonomi Syariah, 2021)
Income in a family determines consumption or expenditure in meeting primary, secondary and tertiary needs. Good Muslim consumption is consumption that has the purpose of the world and the hereafter which is aligned with the income received. The Changes of regional conditions in the form of disasters have an impact on the value of income and consumption priorities for families. The imposition of restrictions on economic activities as well as face-to-face activities echoed by the government has the effect of changing the economic order of the community. Families who are affected by the pandemic are experiencing economic and mental impacts. Such conditions require individuals to behave rationally in their economic activities and be adjusted to Islamic religious guidelines. So that it will form the soul / personality of a pious Muslim. This article uses a descriptive qualitative method. Informants come from communities which are affected by COVID 19 who are in the Education area such as kindergarten, elementary, junior high, high school, and college in Rejomulyo Village. The process of collecting data is done by means of interviews, documentation and observation. Data analysis was done by data triangulation. The results of the study illustrate that rationality in economic activities and the application of Islam includes: changing household consumption during the pandemic along with changes in the income of the head of the family. In addition, the family's understanding of the pandemic is based on the belief that Allah SWT gives a test in the direction of increasing piety.